"Can I get your input with this patient?" Theories for teaching how to seek help from other doctors: Presenter(s): Ching-wa Chung, University of Aberdeen, United Kingdom. (April 2023) - Unknown
Abstract : Background: Seeking advice from, or referrals to, other doctors is a frequent part of most doctor's duties. Yet many junior doctors feel inadequately prepared for this. Current research focuses on postgraduate, not undergraduate medical education. This research addresses this gap with the question What are the emergent theories for the practice of and undergraduate education in Clinical Intraprofessional Communication (CIC)? Methods: Using constructivist grounded theory methodology, nine GPs and eight hospital doctors were interviewed in ten individual interviews and two focus groups. Interviews were transcribed, coded and analysed iteratively. Further theoretical sampling was undertaken to achieve data saturation. Theories were subsequently generated. Findings: 761 initial codes were distilled into 64 focus codes. Two theories emerged. The TRU Perception theory states that the practice of CIC is a product of participants' mutual perception of each other. That is, how participants perceive each other influences the process and outcome of the CIC interaction. Mutual perception is influenced by professional trust, rapport between participants and understanding of each other's clinical role and context. The TuFF Experience theory conveys that the education of CIC should be both experiential and realistic. Learning occurs best by experience. Furthermore, the experiences and skills learnt need to reflect the, sometimes harsh, reality of clinical practice. Factors that affect learning are timing and fidelity of the learning experience as well as feedback to students. Discussion: The TRU Perception theory may help provide a framework to analyse CIC, allowing structured feedback to learners. It can also help inform development of related educational materials. The TuFF Experience theory and model can be used to develop quality learning experiences and even curricular on CIC. Both theories support development of effective undergraduate education in CIC, so that medical students are prepared in this aspect of communication from their first days as junior doctors.